The Andean cosmovision essence in the Teatro campesino: An endo-expansive analysis - Cárdenas Campos, José Manuel (2021)
This article studies the andean worldview in the book Teatro campesino by Víctor Zavala Cataño. In the text, the andean characters are recognized as part of nature and reflect three aspects derived from relationality: "correspondence", "complementarity" and "reciprocity". For this reason, a "endo-expansive" analysis of some andean categories is proposed; that is, we interpret first the essence of the cosmos (kama) until we deal with time and space: the pacha.